Evolution trends and driving factors of industrial water use: A case study of Ordos City, China - Hong Lv; Yiqing He; Yuan Liu; Xinjian Guan; Wenxiu Shang; Zheng Xiaokang (Desalination and Water Treatment)
With rapid industrialization and urbanization, water shortages in China have increasingly constrained industrial development. This study explores the evolution trends and driving factors of industrial water use as a non-engineering approach to mitigate resource distribution imbalances. A high-dimensional control factor identification method was developed, integrating ridge regression, panel Tobit, LMDI, and PSO-SVM techniques. Using Ordos, a key industrial city, as a case study, findings reveal that industrial water consumption rose from 9.11 million m³ in 1990–356.6 million m³ in 2022, with an average annual growth rate of 4 %. The evolution of industrial water use is categorized into three stages, with the third stage showing the highest growth rate. Key driving factors include power generation, heavy industry proportion, and industrial added value, while inhibiting factors involve water recycling rates, sewage reuse, and policy measures. This research offers insights into industrial water dynamics and informs strategies for sustainable water resource management.